Examining the robustness of market risk models - Roque, Roberto Miguel S.; Rey, Mia (Quezon City Cesar E.A. Virata School of Business,University of the Philippines Diliman, 2017)
Reviews Value at Risk (VaR) and Expexted Shortfall (ES), the current industry risk measures, and the usefullness of including Expectiles as a new measure of risk. Results can assist financial institutions, regulators, investors and researchers to gain insights on measuring risk. By acting prudently, financial institutions and regulators create a more stable financial environment which can lead to sustained economic growth and raise the standard of living for it.
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Financial futures -- Mathematical models; Risk management -- Mathematical models; Portfolio management -- Mathematical models